The Protective Role of L-carnitine on Psychosocial Stress-induced Changes in Gene Expression and Protein Levels of Matrix Metalloproteinases, Serum Corticosterone in a Rat Model - Rababa'h, Suzie Y.; Alzoubi, Karem H.; Hammad, Hana; AlQuraan, Laiali; Rababa'h, Abeer M. (CNS & Neurological Disorders - Drug Targets, 2023)
Background: Psychosocial stress (STS) is a common stress in modern societies. Chronic STS is associated with the impairment of a broad range of cognitive functions in humans and with prolonged abnormalities in memory. Matrix metalloproteinases (MMPs), a protein family of zinccontaining endopeptidases, are essential in neuro-inflammation and involved in neurodegenerative diseases. L-Car possessed neuroprotective, antioxidant, and anti-inflammatory properties and was shown to modulate MMPs. Objective: The current study aimed to examine the protective effect of L-Carnitine (L-CAR) on STSinduced changes in serum corticosterone levels, MMP-2, -9, and -12 protein and mRNA expression in the hippocampus as a possible mechanism for L-CAR protective effect on STS-induced memory impairment. Methods: The chronic STS and L-CAR (300 mg/kg/day, i.p) were simultaneously administered for 6 weeks to adult male Wistar rats. Serum corticosterone and protein levels of MMP-2, -9 and -12 were evaluated using ELISA. Real-Time PCR techniques were used to determine the mRNA levels of MMP-2, -9 and -12 in the hippocampus. Results: The findings showed that serum corticosterone levels and MMP-2 and -9 protein levels were significantly increased (p<0.05) in the STS group compared to the control. Similarly, RT-PCR findings showed that the mRNA of those proteinases significantly increased (p<0.05) following the intruder method. On the other hand, the administration of L-CAR restored the alterations in corticosterone levels and MMPs gene and protein expression induced by chronic STS. Conclusion: STS induced elevations in corticosterone and MMP-2 and -9 levels in the hippocampus. L-CAR, on the other hand, exhibited protective effects against the STS-induced changes in MMP-2 and -9.
Keywords: corticosterone